Experimental investigation and theoretical analysis of heat pump systems with two different injection portholes compressors for electric vehicles. (1st January 2017) - Qin, Fei; Zhang, Guiying; Xue, Qingfeng; Zou, Huiming; Tian, Changqing
Highlights: Heat performances of RIASHP system for EVs is designed and tested at −20 °C out-car. Two scroll compressors are used to analyze the effect of injection portholes shapes. Heating capacity of RIASHP system is raised up to 28.6% than traditional system. The refrigerant cycle and injection process and the influence factors are discussed. Summary the analysis: bigger area of injection porthole make better heat capacity. Abstract: The traditional Air Source Heat Pump (ASHP) for Electric Vehicles (EVs) has many limits in cold region because of poor heating performance and operating safety in low ambient temperature, which can be solved by the ASHP with refrigerant injection. A test bench that can be switched between a traditional ASHP system and a refrigerant injection ASHP system for EVs in the cold region is developed in this study. Compressors applied in the test bench are refitted with different injection portholes from the regular electric scroll compressor to analyze the influence of porthole shape on the system performance. The experimental results show that the heating capacity of refrigerant injection ASHP system is raised up by 28.6% compared with the traditional system. The larger injection porthole helps to increase the heating capacity when in-car inlet air temperature is higher, and the effect of injection porthole shapes to injection process and refrigerant cycle is also analyzed. The research will contribute to the application of refrigerant injection technology in EVs.